The Elect Methodists Calvinistic Methodism in England and Wales, 1735-1811. - Jones, David Ceri.; White, Eryn Mant.; Schlenther, Boyd Stanley (Cardiff : University of Wales Press, 2012)
The Elect Methodists is the first full-length academic study of Calvinistic Methodism, a movement that emerged in the eighteenth century as an alternative to the better known Wesleyan grouping. While the branch of Methodism led by John Wesley has received significant historical attention, Calvinistic Methodism, especially in England, has not. The book charts the sources of the eighteenth-century Methodist revival in the context of Protestant evangelicalism emerging in continental Europe and colonial North America, and then proceeds to follow the fortunes in both England and Wales of the Calvin.
'You are only going to a few simple souls': new English Calvinistic groupings, at mid-century'My Lady's society': the birth and growth of the Countess of Huntingdon's Connexion, 1770-1791; 'The Lord's gift to the north': the spread of the movement throughout Wales, 1780-1791; A smooth and satisfactory order': towards a new denomination for Wales and decline in England,1791-1811; Conclusion; Appendix A; Appendix B; Appendix C; Bibliography; Index.
Description based on print version record.
Keywords: Methodism; Methodist Church -- Great Britain; Religion; Calvinistic Methodists -- England -- History -- 18th century; Calvinistic Methodists -- England -- History -- 19th century; Calvinistic Methodists -- Wales -- History -- 18th century; Calvinistic Methodists -- Wales -- History -- 19th century; RELIGION / Christianity / Methodist; Electronic books